KARAKTERISTIK SIFAT-SIFAT KIMIA DAN ORGANOLEPTIK KUE KERING BERBAHAN DASAR PATI SAGU, UBI KAYU, UBI JALAR DAN KELADI - Febby J Polnaya; Rachel Breemer (Universitas Pattimura, 2016)
The purpose of this research was to characterize chemical and sensory properties (color, texture, taste and liking) of starch-based sago, cassava, sweet potato and cocoyam cookies. Analysis of cookies include moisture content, ash, fat, protein, crude fiber and sensory analysis including color, texture, taste and likeness). The proximate composition indicated that the water content of cookies varied between 1.48 to 2.05%, ash content of 0.65 to 0.72%, 19.23 to 21.76% of fat, crude fiber from 0.41 to 0.71% and 1.33 to 2.42% of total protein. Based on organoleptic tests, the color of cookies was yellow to brownish-yellow, with crispy texture, the taste was sweet and were mostly preferred.